FORMULASI KRIM EKSTRAK ETANOL DAUN LAMUN (Syringodium isoetifolium) - Juwita, Anisa Puspa; Yamlean, Paulina V.Y; Edy, Hosea Jaya (PHARMACON, 2013)
Seagrass (Syringodium isoetifolium) is a plant that lives submerged at sea, this flowering plant, leaves, and stems that are plugged into a powerful in water. The chemical content of the leaves of the Seagrass is a flavonoid, phenol, hydroquinone, and antioxidants.This study aims to determine the quality of the cream of seagrass leaf extracts using a concentration of 5%, 10%, 20% dan 40%. on organoleptic testing conducted cream, homogeneity test, test dispersive power, pH and absorbance test. results obtained in the organoleptic seen from the color green, semi-solid dosage forms and distinctive smell seagrass cream. homogeneity test. homogeneity test cream seagrass leaf extract with a concentration of 5% 10% 20% and 40% did not experience any clumping or phase separation dispersive power test creams ranged from 2.5 cm - 3.5 cm. pH ranged from 4.93 - 5.96 and test absorption ranged from 3.7 ml - 5 ml. seagrass leaf extract cream with type W/O creams that meet the test of homogeneity test quality, dispersive power test, test and test pH absorption Keyword : Syringodium isoetifolium, Seagrass Leaves, Cream W/O